Antipsychotic drug use in nursing home residents with and without dementia: keep an eye on the pro re nata medication. (July 2017) - Allers, Katharina; Dörks, Michael; Schmiemann, Guido; Hoffmann, Falk
Abstract : Behavioral and psychological symptoms of dementia often lead to the prescription of antipsychotics, especially in nursing homes, but their use remains controversial. This study aimed to assess antipsychotic drug use in residents with dementia compared with those without dementia. Data were obtained through the cross-sectional 'inappropriate medication in patients with renal insufficiency in nursing homes' (IMREN) study including data from 21 nursing homes. Descriptive statistics were used and factors associated with the prescription of antipsychotics were identified by logistic regression. Overall, 57.5% of the 837 residents had a diagnosis of dementia and 47.0% of residents with dementia and 19.5% of those without dementia received antipsychotics. 35.9% of all antipsychotics in residents with dementia were prescribed as pro re nata (PRN) compared with 23.0% for residents without dementia. Typical antipsychotics were prescribed more commonly than atypical ones. The adjusted logistic regression showed a significant association between the prescription of antipsychotics and dementia (odds ratio: 3.58, 95% confidence interval: 2.45–5.25) as well as severe care dependency (odds ratio: 1.68, 95% confidence interval: 1.10–2.55). Despite safety warnings, antipsychotics are still frequently prescribed to residents with dementia. Almost half received antipsychotics and about a third of the antipsychotics are prescribed as PRN. Further studies should assess the use of PRN antipsychotics and guidelines for PRN prescriptions are clearly needed.